ANALISIS DAMPAK DITERAPKANNYA KEBIJAKAN WORKING FROM HOME SAAT PANDEMI COVID-19 TERHADAP KONDISI KUALITAS UDARA DI JAKARTA - Umara Firman Rizi D; Suradi; Sunaryo; Andriyani Agus; Mizani Ahmad; Sheila Dewi Ayu Kusumaningtyas; Hanifah Nurhayati; Aulia Nisa’ul Khoir; Cici Sucianingsih; Nur Faris Prih W (Jurnal Meteorologi Klimatologi dan Geofisika, 2019)
The purpose of this study is to examine the effect of the implementation of policies on reducing human activity regarding the covid-19 outbreak to the concentration of air pollution in March 2020 in the Jakarta area using a comparison of the time series of PM10 and PM2.5 hourly calculations calculated to be the daily average in March by applying the Pearson correlation equation and scatter diagram to obtain a pattern of relationships in the form of positive, negative or non-linear and the degree of weak, strong or perfect relationship between variables. The main contributions of this research are as follows: Evaluation of the significance of the decrease in the concentration value of the average PM10 and PM2.5 in March 2020 with a correlation to March variables in the previous year based on the acquisition of qualitative results in the form of a graph of the trend of decreasing PM10 and PM2.5 in March 2020 compared to March of the previous year and quantitative in the form of a negative correlation with the Pearson moment and scatter diagram showing a decrease in March 2020 compared to March of the previous year so that the policy of reducing human activity in a response to the Covid-19 pandemic has an impact on a better air quality condition in Jakarta.